The profile of electronic cigarette users in Turkey - Goney, Gulsen; Topdemir, Aykut; Nal, Burcu (Wolters Kluwer Medknow Publications, 2019)
OBJECTIVE: Data on electronic cigarette (e-cigarette) use patterns are limited worldwide. This paper examines user profile of e-cigarettes in Turkey. MATERIALS AND METHODS: This is a descriptive study. E-cigarette users >= 18 ages) in Turkey were asked to participate in a web-based survey. The participants provided information on their use history, patterns of e-cigarette use, content of e-liquid (amount of nicotine, types of food additives, kinds of products purchased, etc.), attitudes regarding the product, and information on the concurrent use of classic cigarettes. RESULTS: The online questionnaire was completed by 480 e-cigarette users. The results indicated that e-cigarette users have high incomes (100%), previous smoking dependency (100%), and a mean age of 35 +/- 6, and the majority of them are male (99.2%). They use e-cigarettes primarily to quit smoking or to reduce the harm associated with smoking (65.4%, 11.1%, respectively). The e-cigarette users (15.6%) intend to quit smoking by gradually reducing their e-liquid nicotine concentrations. The majority of them (76%) think that e-cigarettes and e-liquids could be harmful to children. Of them, 46.6% used second-generation e-cigarettes and 53.3% used third-generation e-cigarettes with direct dripping. CONCLUSION: This study is the first description of the attitudes and use of e-cigarette users in Turkey. Results show that most of the users began to use e-cigarettes in order to quit smoking. According to the study findings, we propose an urgent need for an evaluation by health authorities for e-cigarette use and smoking cessation.
Keywords: Cigarettes; e-cigarettes; electronic cigarettes; electronic nicotine delivery systems; online questionnaires